Puerarin Inhibits Ferroptosis and Inflammation of Lung Injury Caused by Sepsis in LPS Induced Lung Epithelial Cells - Xu, Baiye; Wang, Haidao; Chen, Zhen (Frontiers in Pediatrics, 2021)
Background: Ferroptosis is a new type of programmed cell death, which plays an important role in lung injury caused by sepsis. Studies have reported that Puerarin (Pue) can treat lung injury caused by sepsis in children, but whether it plays a role by regulating iron death has not been reported. Methods: LPS induced human alveolar epithelial cell A549 to form a model of lung injury caused by sepsis. MTT detected the effect of Pue on A549 cell viability and the effect of Pue on LPS-induced A549 cell viability. The effects of Pue on LPS-induced inflammatory cytokines TNF-α, IL-8, IL-1β in A549 cells were determined by ELISA assay. The expression level of MDA was detected by TBARS colorimetric quantitative detection kit. GSH kit was used to detect the expression of GSH in cells. The iron kit detected the total iron level and the expression level of ferric divalent ions in the cells. DCFH-DA fluorescent probe was used to detect ROS levels. Western blot was used to detect the expression of ferroptosis-related proteins in cells. Results: Pue alleviated LPS-induced injury and inflammatory response in A549 cells, and Pue reduced the expression of ROS, MDA and GSH in LPS-induced A549 cells. In addition, Pue reduced total iron levels and ferrous ion levels in LPS-induced A549 cells, and decreased the expression of iron ferroptosis-related proteins. Conclusion: Puerarin inhibited ferroptosis and inflammation of lung injury caused by sepsis in children in LPS induced lung epithelial cells.